The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.22271/j.ento.2023.v11.i1a.9150
|View full text |Cite
|
Sign up to set email alerts
|

Lebadea Martha febricius, 1787 – Knight (Lepidoptera: nymphalidae), The first report from, Namdapha National Park, Miao, Arunachal Pradesh

Abstract: Present study reported the discovery of butterfly species Lebadea Martha Febricius, (1787) -Knight for the first time in Namdapha National Park, Miao, Changlang District, Arunachal Pradesh. Basic morphology of the species confirmed the identification. However, the occurrence is not surprising as half of the landscape of Miao is covered with forest and this species generally confined to forest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Variya et al (2021) reported the occurrence of the Veined Palmer Hidari bhawani Nicéville, [1889] from Namdapha NP & TR, Miao, Arunachal Pradesh. Species Lebadea martha (Fabricius, 1787) is reported for the first time in Arunachal Pradesh from Namdapha National Park, Miao (Upadhaya & Gogoi, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Variya et al (2021) reported the occurrence of the Veined Palmer Hidari bhawani Nicéville, [1889] from Namdapha NP & TR, Miao, Arunachal Pradesh. Species Lebadea martha (Fabricius, 1787) is reported for the first time in Arunachal Pradesh from Namdapha National Park, Miao (Upadhaya & Gogoi, 2023).…”
Section: Introductionmentioning
confidence: 99%